ANALISIS RESIDU PESTISIDA GOLONGAN PIRETROID PADA BEBERAPA SAYURAN DI KOTA MERAUKE - Yorinda Buyang; Yenni Pasaribu (Universitas Musamus, Merauke, Papua, 2014)
The aim of this research was to know the level of pesticide residue in the vegetables in local market in Merauke. There were six pesticide residues from pyrethroid group tested on three kinds of vegetables, i.e. cabbages (Brassica oleracea), long beans (Vigna Sinensis (L.) Savi Ex Has), and mustard greens(Brassica sinensis L.)from the local market in Merauke. The research was conducted in Laboratory of Agrochemical Residue of Bogor Agricultural Environment Research Center.Pesticide residue was analyzed by using gas chromatography (GC).The results showed that pesticide residues from all vegetables were lower than maximum residue limit (MRL), hence it was relatively safe for consumption